Genetic susceptibilty and celiac disease: what role do HLA haplotypes play? - Martina, Sciurti (Acta Biomed, 2018)
Celiac disease is a chronic immune-mediated enteropathy triggered by exposure to dietary gluten in genetically predisposed individuals. Many genes involved in the pathogenesis have been identified and a crucial role is known to be played by the Human Leukocyte Antigen (HLA) system. The main determinants for genetic susceptibility are HLA-DQA1 and HLA-DQB1 genes encoding for HLA-DQ2 and HLA-DQ8 molecules, carried by almost all patients affected. However, since HLA-DQ2 and HLA-DQ8 heterodimers explain almost 40% of the disease heritability, HLA typing should not be applied in diagnosis, but exclusively to clarify uncertain diagnoses, considering its negative predictive value. (www.actabiomedica.it)